Policy on the financial management pattern of the Regional Public Service Agency (PPK-BLUD) at the Soreang Community Health Center Bandung District - Casmita, Dede; Sumadinata, Widya Setiabudi; Alexandri, Mohammad Benny (Technium Social Sciences Journal, 2021)
The purpose of this study is to find out, examine, analyze, and understand in depth the implementation of the Policy on the Financial Management Pattern of the Regional Public Service Agency (PPK-BLUD) at the Soreang Community Health Center, Bandung Regency. Data collection techniques were carried out using interviews, observation, and recording of documents related to Policy Implementation. The main data source in this research is semi-structured interviews. The data obtained is then analyzed qualitatively by examining all the data that has been collected with indicators of policy implementation, namely three main activities, namely organizational activities, interpretation activities, and application activities. The results showed that the implementation of the policy from the number of human resources managing the Regional Public Service Agency (BLUD) of the Soreang Community Health Center, Bandung Regency had met the needs, but viewed from the competence of human resources it had not met the needs. This can be seen by the presence of several managerial positions that have multiple positions and do not match the required educational qualifications. Then, they do not fully understand the substance of the policy, the meaning of the policy, and the purpose of the policy, so that the interpretation is different. However, in general, the communication and internal coordination of the Soreang Community Health Center went well. To increase the competence of the employees of the Regional Public Service Agency (BLUD) the Soreang Community Health Center has not independently assigned or sent employees to attend training, especially in the administrative and financial administration sections. But it still depends on the schedule of activities provided by the Bandung District Health Office.